2020
DOI: 10.48550/arxiv.2002.06754
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Velocity Gradient in the Presence of Self-Gravity: Identifying Gravity-induced Inflow and Determining Collapsing Stage

Yue Hu,
Alex Lazarian,
Ka Ho Yuen

Abstract: Understanding how star formation is regulated requires studying the energy balance between turbulence, magnetic fields, feedback, and gravity within molecular clouds. However, identifying the transition region where the gravity takes over and collapse occurs remains elusive. Recent studies of the Velocity Gradient Technique (VGT), which is an advanced tool for magnetic field studies, reveal that the velocity gradient changes its direction by 90 • with respect to the magnetic field in the regions of gravitation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…When one measures the gradients of a highly self-gravitating molecular cloud, they follow the direction of the infall, i.e. the direction of gradients flips 90 • becoming parallel to the magnetic field 46,50 . This happens because the acceleration of the fluid points toward the core of the collapsing region, thus the direction of the magnetic field and of fluid motions induced by gravitational infall become parallel.…”
Section: Gravitational Collapsementioning
confidence: 99%
“…When one measures the gradients of a highly self-gravitating molecular cloud, they follow the direction of the infall, i.e. the direction of gradients flips 90 • becoming parallel to the magnetic field 46,50 . This happens because the acceleration of the fluid points toward the core of the collapsing region, thus the direction of the magnetic field and of fluid motions induced by gravitational infall become parallel.…”
Section: Gravitational Collapsementioning
confidence: 99%
“…Another particular situation for VGs and IGs is the self-gravity. Hu et al (2020) numerically demonstrated that the inflow induced by gravitational collapse could flip the orientation of both IGs and VGs by 90 degrees, from perpendicular to parallel to the magnetic field. This phenomenon has been observed in the molecular clouds NGC 1333 and Serpens (Hu et al 2019d).…”
Section: Velocity and Intensity Gradient Techniquesmentioning
confidence: 99%
“…According to Hu et al (2020), the relative orientation between the magnetic field as inferred from dust polarimetric observations and the velocity and intensity gradients of the gas emission can be used as an indicator of the undergoing dynamical processes:…”
Section: Coupling Between Magnetic Field Structure and The Cloud's Dy...mentioning
confidence: 99%
“…These studies have shown a good correspondence between the magnetic field directions inferred using VGT and that obtained from polarimetry, e.g. with the Planck, BLASTPOL, and HAWC+ data (Hu et al 2019;Alina et al 2022;Hu et al 2020Hu et al , 2021. The property of intensity gradients being related to magnetic field direction has also been used in the developments of Koch et al (2012) to infer magnetic field direction in molecular clouds.…”
Section: Introductionmentioning
confidence: 68%